(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Gestational Diabetes Mellitus (GDM) is the most common metabolic disorder during pregnancy and is associated with increased maternal and neonatal morbidity. There are many serum markers known to be associated with Gestational Diabetes Mellitus (GDM). High serum ferritin level has been associated with the risk of developing gestational diabetes mellitus. The aim of the study was to investigate the association of serum ferritin levels with GDM. Materials and methods: This case control study was carried out in the Department of Obstetrics & Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka, Bangladesh between February 2018 and January 2019. A total of 120 pregnant women between 18 and 35 years of age attending outdoor antenatal clinic in their second or third trimester of pregnancy were included in this study. Among them 60 diagnosed cases of GDM were consider as group A and rest 60 (Without GDM) were considered as group B. Serum ferritin concentration was measured in all of these patients. Statistical analysis of the results was obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-22). Results: The mean serum ferritin level was 124.1±14.7 ng/ml and 87.4±18.9 ng/ml in group A and group B respectively. The difference was statistically significant (p<0.05) between two groups. More than half (55.0%) patients had serum ferritin level >120 ng/ml in group A and 15(25.0%) in group B. Serum ferritin level >120 ng/ml had 3.67 (95.0% C.I. 1.58 to 8.60) times significantly (p<0.05) increase to developed gestational diabetes mellitus. There was a significant positive correlation between serum ferritin and fasting plasma glucose (r=0.445, p=0.001) in GDM patients. Similarly, a significant positive correlation between serum ferritin and 2-h after plasma glucose level following 75g oral glucose (r=0.427, p=0.001) in GDM patients. Conclusion: A significant positive association was found between GDM and maternal serum ferritin levels. JCMCTA 2022 ; 33 (1) : 154-159